2011
DOI: 10.1111/j.1528-1167.2011.03299.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct correlation between the facial nerve nucleus and hemifacial seizures associated with a gangliocytoma of the floor of the fourth ventricle: A case report

Abstract: SUMMARYA dysplastic neuronal lesion of the floor of the fourth ventricle (DNFFV) causes hemifacial seizures (HFS) from early infancy. However, it is still controversial whether HFS is generated by the facial nerve nucleus or cerebellar cortex. In this study, we confirm a direct correlation between the rhythmic activities in the DNFFV and HFS using intraoperative electroencephalography (EEG) and electromyography (EMG) monitoring. Our results support the theory that a DNFFV provokes ipsilateral HFS via the facia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…15 Since then there have been a number of cases demonstrating that cerebellar seizures can occur. [1][2][3][4][5][6][7][8][9][10][11]13,14,16,19 In this article we document 2 such patients. The first is a child with a hypodense lesion on MRI deep in the cerebellum resulting in complex partial seizures that were eventually medically controlled.…”
mentioning
confidence: 99%
“…15 Since then there have been a number of cases demonstrating that cerebellar seizures can occur. [1][2][3][4][5][6][7][8][9][10][11]13,14,16,19 In this article we document 2 such patients. The first is a child with a hypodense lesion on MRI deep in the cerebellum resulting in complex partial seizures that were eventually medically controlled.…”
mentioning
confidence: 99%
“…Furthermore, gangliogliomas are among the most common epileptogenic lesions in epilepsy centers [21], harboring a major propensity for spontaneous electrical discharges which probably explains the association of this lesion to this unique syndrome [22]. Not unexpectedly, histological studies of cerebellar or fourth ventricle lesions presenting with subcortical epilepsy were classified as ganglioglioma [2,4,9,10,12,[23][24][25][26][27], hamartoma [8,13,14,28], gangliomatous hamartoma [29], ganglioneurocytoma [30][31][32] or low-grade dense fibrillary astrocytoma [3,15]. Although many of these lesions may carry a developmental origin and actually represent a continuum with FCD, some are not intrinsically epileptogenic [33].…”
Section: Discussionmentioning
confidence: 95%
“…1D). Intralesional EEG recordings (Delande et al, 2001;Harvey et al, 1996;Yagyu et al, 2011) have been performed in some cases and have shown direct correlation between intralesional rhythmic activity and ipsilateral hemifacial seizures (Yagyu et al, 2011). Furthermore, DSI tractography, portrayed an anatomical disruption at the lesion level (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study, using concomitant iEEG and electromyographic recordings, implied that hemifacial contractions originate in the ipsilateral cerebellar dysplastic area and propagate via the facial nucleus into the ventrolateral region of the inferior pons (Yagyu et al, 2011). In order for this to occur, aberrant cerebello-pontine connections are required as normal cerebellar output is rubro-cortical or thalamo-cortical.…”
Section: Discussionmentioning
confidence: 99%